Russian ruble exchange rate: Modeling of comparative medium-term and long-term dynamics - A. Yu. Kuzmin (Финансы: теория и практика, 2021)
The subject of the study is the dynamic mechanism of the formation of the exchange rate of the Russian ruble in a multilevel system of economic fundamental determinants-aggregates in the context of the independent ﬂoating rate of the national currency. The aim of the study is to develop the author’s theoretical and methodological conceptual approach to modeling the dynamics of the equilibrium exchange rate based on international ﬂows (IFEER) and to develop a new model of the Russian ruble exchange rate dynamics on its basis. The methodological base of the research includes system analysis, fundamental methods of economic theory, classical methods of mathematical analysis, and economic and statistical analysis, and the provisions of national accounting. The paper presents data on the verifcation of the results of modeling mediumterm equilibrium dynamics. At the same time, the author pays considerable attention to the mathematical modeling of the long-term dynamics of the ruble exchange rate in comparison with the medium-term equilibrium dynamics and the mathematical analysis of internal functional relationships in modern conditions, which determines the scientifc novelty and relevance of the study. Based on the conducted mathematical modeling, the author concludes about the trends of a stronger ruble exchange rate in the long run, while maintaining the current long-term trends.